The stereotype content model and mental disorders: Distinct perceptions of warmth and competence - Allstadt Torras, Ramona C.; Scheel, Corinna; Dorrough, Angela R. (Frontiers in Psychology, 2023)
This work investigates the perception of eight different mental disorders within the Stereotype Content Model (SCM). The presented study (N = 297) includes a sample representative for the German population in terms of age and gender. Results reveal distinct warmth and competence evaluations for people with different mental disorders, e.g., people with alcohol dependence were seen as less warm and less competent than people with depression or phobia. Future directions and practical implications are discussed.